TRANSLATION AND FOREIGN LANGUAGE TEACHING - Roza, Melinda (Department of English Education of STAIN Jurai Siwo Metro, 2015)
Abstract: Translation is one of the difficult skill since it need other skill to support the activities. That is why teachers sometimes deny this skill to be applied in the classroom teaching. Also, the activities takes times too much because the studentsâ ability are not the same. However, despite of the limitation, there are some advantages of implementing translation technique in the classroom. It can be used as the technique to teach the four foreign language skills as well as to teach the translation skill itself. This article suggests two models of implementing translation in the language classroom. The first is to apply translation as a method or technique in order to teach the four skills of foreign language. In this model, the translation result is not being assessed since the purpose is not the translation itself but the ability of the four language skills. The other is the model where translation is being conducted outside of the classroom. Thus, the classroom activities become pre-translation step since it is only about discussing the material to be translated at home. This model assessed the studentsâ translation result. So, by having these two models, it is shown that translation is a good skill to be implemented in the language classroom.Keywords: translation, translation activities, translation technique in language teaching